2020
DOI: 10.1126/sciadv.abb1112
|View full text |Cite
|
Sign up to set email alerts
|

Self-targeting, zwitterionic micellar dispersants enhance antibiotic killing of infectious biofilms—An intravital imaging study in mice

Abstract: Extracellular polymeric substances (EPS) hold infectious biofilms together and limit antimicrobial penetration and clinical infection control. Here, we present zwitterionic micelles as a previously unexplored, synthetic self-targeting dispersant. First, a pH-responsive poly(ε-caprolactone)-block-poly(quaternary-amino-ester) was synthesized and self-assembled with poly(ethylene glycol)-block-poly(ε-caprolactone) to form zwitterionic, mixed-shell polymeric micelles (ZW-MSPMs). In the acidic environment of staphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 61 publications
0
56
0
Order By: Relevance
“…Using this technique, we have recently shown that it takes pH‐responsive zwitterionic micelles composed of poly(ethylene glycol) and poly(ϵ‐caprolactone) block co‐polymers at least 20 min to reach an intra‐abdominal infection site after tail‐vein injection. [25] Collectively, and within the limitations of different infection sites, infecting bacterial strains and probing molecules and particles, these comparisons points to the superiority of water as a pH‐responsive functionality on nanocarriers for self‐targeting to an infection site.…”
Section: Resultsmentioning
confidence: 99%
“…Using this technique, we have recently shown that it takes pH‐responsive zwitterionic micelles composed of poly(ethylene glycol) and poly(ϵ‐caprolactone) block co‐polymers at least 20 min to reach an intra‐abdominal infection site after tail‐vein injection. [25] Collectively, and within the limitations of different infection sites, infecting bacterial strains and probing molecules and particles, these comparisons points to the superiority of water as a pH‐responsive functionality on nanocarriers for self‐targeting to an infection site.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, numerous other detection methods are under development and efforts should be made to allow these technologies to translate into the clinic ( Achinas et al., 2020 ; Parlak and Richter-Dahlfors, 2020 ). Among them, recently there has been the successful use of imaging technologies using bioluminescence ( Chauhan et al., 2016 ; Hoffmann et al., 2019 ; Maiden et al., 2019 ; Gordon et al., 2020 ; Kreth et al., 2020 ; Redman et al., 2020 ; Van Dyck et al., 2020 ) or intravital imaging ( Thanabalasuriar et al., 2019 ; Abdul Hamid et al., 2020 ; Gries et al., 2020 ; Tian et al., 2020 ) to study the effect of antimicrobial agents on biofilms or the behavior of immune cells in contact with biofilms in various in vivo models of biofilm-related infections.…”
Section: Challenges In Methods For Investigating Biofilmsmentioning
confidence: 99%
“…[23] Direct observation of pH-driven self-targeting of antimicrobial nanoparticles to an infection site in vivo has,t ot he best of our knowledge,o nly been made possible through the use of intra-vital imaging, [24] as applied here.U sing this technique, we have recently shown that it takes pH-responsive zwitterionic micelles composed of poly(ethylene glycol) and poly(ecaprolactone) block co-polymers at least 20 min to reach an intra-abdominal infection site after tail-vein injection. [25] Collectively,a nd within the limitations of different infection sites,i nfecting bacterial strains and probing molecules and particles,these comparisons points to the superiority of water as ap H-responsive functionality on nanocarriers for selftargeting to an infection site. Similarly,s elf-targeting of DCPA-H 2 Ol iposomes into as olid tumor was investigated after tail-vein injection of rhodamine loaded liposomes in mice (Figure 5e,f ).…”
Section: Forschungsartikelmentioning
confidence: 98%